First report of Ceratomyxa scorpaeni (Cnidaria: Myxozoa) from Scorpaena porcus in the Black Sea - Okkay Sevi̇lay; Gürkanli, C. Tolga; Çi̇ftçi̇ Yilmaz; Yurakhno Vi̇oletta; Özer, Ahmet (Zootaxa, 2021)
Members of the class Myxosporea Bütschli, 1881 have a cosmopolitan distribution in a wide variety of fish species worldwide. In the present study, the black scorpionfish Scorpaena porcus collected from the Sinop coasts of the Black Sea was investigated for myxosporean parasites using both conventional and molecular methods in the period between September 2015 and August 2019. Using morphological and morphometric data, the myxosporean parasite Ceratomyxa scorpaeni Garbouj, Rangel, Castro, Hmissi, Santos, Bahri, 2016 was identified in the gall bladder of host fish. Molecular analysis of the 18S rDNA gene confirmed the identity of this parasite as C. scorpaeni. This is the first report of its occurrence in the Black Sea.